Diagnostic accuracy of 64 multislice CT angiography in the assessment of coronary in-stent restenosis: A meta-analysis - Sun, Zhonghua; Almutairi, Abdulrahman (Elsevier Ireland Ltd, 2010)
Purpose: The aim of this study was to perform a meta-analysis of the diagnostic accuracy of 64-slice CT angiography for evaluation of coronary stent restenosis in patients treated with coronary stents when compared to conventional coronary angiography. Materials and Methods: A search of PUBMED/MEDLINE databases for English literature was performed. Only studies comparing 64-slice CT angiography with conventional coronary angiography for the detection of coronary in-stent restenosis (more than 50% stenosis) were included for analysis. Sensitivity and specificity estimates pooled across studies were tested using a fixed effects model. Fourteen studies met selection criteria for inclusion in the analysis. The mean value of assessable stents was 89%. Prevalence of in-stent restenosis following coronary stenting was 20% among these studies. Pooled estimates of the sensitivity and specificity of overall 64-slice CT angiography for the detection of coronary instent restenosis was 90% (95% CI: 86%, 94%) and 91% (95% CI: 90%, 93%), respectively, based on the evaluation of assessable stents. Diagnostic value of 64-slice CT angiography was found to decrease significantly when the analysis was performed with inclusion of nonassessable segments in five studies, with pooled sensitivity and specificity being 79% (95% CI: 68%, 88%) and 81% (95% CI: 77%, 84%). Stent diameter is the main factor affecting the diagnostic value of MSCT angiography. Conclusion: Our results showed that 64-slice CT angiography has high diagnostic value (both sensitivity and specificity) for detection of coronary in-stent restenosis based on assessable segments when compared to conventional coronary angiography.